مواقف العاملين اساس لتحقيق المشاركة المعرفية دراسة حالة مجمع صيدال - عيشوش, عواطف (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الدراسة إلى تحديد واقع واختبار مدى مساهمة مواقف العاملين في تحقيق المشاركة المعرفية بمجمع صيدال، مستخدمين الاستبيان كأداة لجمع المعلومات، فقمنا بتوزيعه على عينة عشوائية مقدارها 100عامل، وكان عدد الاستبيانات المسترجعة والصالحة للتحليل الإحصائي90 استبان، استخدم في التحليل الإحصائي للبيانات عدة أساليب إحصائية، ولقد خلصت الدراسة بنتيجة مفادها وجود علاقة إيجابية بين مواقف العاملين والمشاركة المعرفية. This study aimed to determine the facts and to test the extent to which employees’ attitudes contribute to knowledge sharing in compound of Saidal, using the questionnaire as a tool to gather information, so we distributed to a random sample of 100 workers. The numbers of questionnaires that are recovered and valid to statistical analysis are 90 questionnaire . Several statistical methods are used in statistical analysis of information. Was concluded result at that the existence of a positive relationship between Employee Attitudes of in the sharing knowledge. Keywords: sharing knowledge, Employee Attitudes, compound of Saidal.
مقال
Keywords: المشاركة المعرفية ; مواقف العاملين ; مجمع صيدال